Microtopography features of intramedullar cranio-spinal tumors - Trosh, R. M.; Shamayev, M. I.; Slinko, E. I.; Gudkov, V. V.; Lisiany, A. N.; Verbov, V. V. (Ukrainian Neurosurgical Journal, 2007)
The microanatomy and topography features of intramedullar cranio-spinal tumours were studied. Various microanatomy and topography variants of intramedullar cranio-spinal tumours were given. The necessity to emanate from various types of intramedullar cranio-spinal tumors localization and their interactions with neurovascular structures in this area was proved at treatment and surgical interventions planning, that allowed to decrease considerably postoperative complications.